Late diagnosis of Alstrom syndrome in a Yemenite-Jewish child. (2nd January 2019) - Weiss, Shirel; Cohen, Lior; Ben-Yosef, Tamar; Ehrenberg, Miriam; Goldenberg-Cohen, Nitza
ABSTRACT: Background : We describe the ophthalmologic, clinical, and genetic findings in a patient of Yemenite-Jewish origin diagnosed with Alstrom syndrome due to a novel splice-site mutation 10 years after a clinical misdiagnosis of Leber congenital amaurosis. Methods : Ophthalmological evaluations included visual acuity, cycloplegic refraction, slit-lamp, and optical coherent tomography. Genetic analyses included whole exome sequencing followed by bioinformatics analysis and segregation analysis. An in vitro splicing assay was used to evaluate the effect of the identified mutation on splicing. Taqman assay was used to determine the need for population screening for the identified mutation. Results : Ophthalmologic findings at age 6 were impaired vision, nystagmus, and hyperopia. At age 16 years, the patient presented with obesity, hypothyroidism, and elevated transaminase levels in addition to reduced vision, wandering nystagmus, disc pallor, and degenerative retinal changes. Targeted genetic analysis of ALMS1 revealed a homozygous transversion, c.11544 + 3A>T, suggesting a novel splicing mutation, with elimination of the donor splice site and insertion of 73 nucleotides at the end of exon 16. These changes were validated by Sanger sequencing and co-segregation on family members. Conclusions : Ophthalmologists should be alert to the differential diagnosis of inherited retinal degeneration in young patients who present with impaired vision, especially if systemic symptoms are mild and there is no known family history. In the present case, targeted genetic analysis of a child with a syndromic cone-rod dystrophy yielded a novel splicing mutation in ALMS1 causing Alstrom syndrome.